2015
DOI: 10.1039/c5sc01013f
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reconstitution of α-pyrone ring formation in myxopyronin biosynthesis

Abstract: α-Pyrone rings exist in many polyketide synthase (PKS) derived natural products. We report the first in vitro reconstitution of α-pyrone ring formation by a type I PKS using chemically synthesized substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 35 publications
(59 reference statements)
2
46
0
Order By: Relevance
“…In particular, some of the ketosynthases involved in bacterial pyrone biosynthesis create an ␣-pyrone ring with large orthogonal substituents, including the antibiotics myxopyronin, corallopyronin, and pseudopyronin (17,24,25). The orthogonal nature of the substituents matches well with the orthogonal alkyl channels observed in OleA, as was noted in the recent crystal structure of Myxococcus fulvus Mx f50 MxnB, the stand-alone ketosynthase that completes myxopyronin biosynthesis (26). The alkyl chains in both OleA alkyl channels A and B are not linear but curled, explaining how different lengths of alkyl chain can be accommodated in the active site and why X. campestris OleA is promiscuous (3).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In particular, some of the ketosynthases involved in bacterial pyrone biosynthesis create an ␣-pyrone ring with large orthogonal substituents, including the antibiotics myxopyronin, corallopyronin, and pseudopyronin (17,24,25). The orthogonal nature of the substituents matches well with the orthogonal alkyl channels observed in OleA, as was noted in the recent crystal structure of Myxococcus fulvus Mx f50 MxnB, the stand-alone ketosynthase that completes myxopyronin biosynthesis (26). The alkyl chains in both OleA alkyl channels A and B are not linear but curled, explaining how different lengths of alkyl chain can be accommodated in the active site and why X. campestris OleA is promiscuous (3).…”
Section: Discussionsupporting
confidence: 52%
“…2A), consistent with this binding the first substrate and thus the covalent acyl-enzyme intermediate prior to condensation. Interestingly, Sucipto et al (26) suggested that in MxnB the first substrate would bind in alkyl channel B based on the steric constraints required for ␣-pyrone ring formation.…”
Section: Discussionmentioning
confidence: 99%
“…One central aim is to elucidate unknown biosynthetic steps and to identify and study the corresponding biocatalysts. Important examples include the identification of enzymes responsible for cyclocondensations to yield tetramate ring systems from one thioester-activated polyketide chain (Gui et al, 2015;Sims and Schmidt, 2008), or pyrone ring systems from two chains (Sucipto et al, 2015;Zocher et al, 2015). A tandem mass spectrometrybased analysis granted insight into a double-bond shift during corallopyronin biosynthesis (Lohr et al, 2013).…”
Section: Applications Of Nac Thioestersmentioning
confidence: 99%
“…Other structurally characterized thiolase superfamily enzymes, such as FabH, PKS type II, and HMG-CoA synthase condense smaller substrates and only require two (FabH and PKS type II) or one (HMG-CoA synthase) substrate binding channels, respectively [14, 16, 18, 19]. The only thiolase superfamily enzymes known to require three distinct channels are OleA and pyrone and pseudopyrone ketosynthases [17, 20]. It has been proposed that these enzymes also utilize an active site general base, a glutamate, that comes from the second subunit of the dimer to initiate Claisen condensation, but this has never been demonstrated [17, 21].…”
Section: Introductionmentioning
confidence: 99%